THE EFFECT OF RADIATION ON THE HUMAN BODY AND METHODS OF PROTECTION (The Conference Hub, 2025)
In the modern era of scientific and technological progress, radiation has become an integral part of human activity. It is widely used in medicine, energy, industry, and scientific research. Radioisotopes are applied in the diagnosis and treatment of diseases, particularly in radiotherapy and nuclear medicine, as well as in quality control of materials and the generation of electrical energy. However, despite its undeniable benefits, uncontrolled exposure to ionizing radiation can pose a serious threat to human health and the biosphere as a whole. The key challenge of contemporary society is the responsible and safe use of radiation technologies in the interest of health and sustainable development.